Nationalism and Internationalism in India - Amrita Dey, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Nationalism in India was born out of the bondage of a country subjected to foreign rule and the internal loss of self-confidence that went with such a rule. The freedom struggle that followed was understood to be Indian nationalism, not Hindu or Muslim or any kind of religious or other nationalism primarily aimed to ensure the welfare of all citizens and their entitlement to justice and human rights. The present paper examines this evolution of nationalism in India as a freedom struggle against the British and then as a democratic process to give every Indian a voice in decision-making in free India. But what has been noticed over the years is a steady regression in secularism where individual rights were compromised, then as a struggle for power in party circles and finally in the name of religion. To the extent that today’s nationalism in India is perceived more as an imposed ‘feeling’- a feeling that has equally impacted the country’s image outside home; despite promising strides to transform India from a ‘balancing’ to a ‘leading’ power internationally. Being normative in nature the paper borrows citation mostly from secondary sources of information, including books, journals and e-sources for current affairs. It tries to incorporate two formal discussions on Nationalism and International status of India which is part of the curriculum at UG-level in college/universities.Received 9thDecember 2020; Revised 2nd March 2021; Accepted 20th March 2021